DYNAMICS OF THE MECHANISM FOR VENTILATION ACROSS FEATHERS IN FLAPPING WING UAV - Silva, Renan Cavenaghi [UNESP]; Bueno, Douglas D. [UNESP] (My University, 2024)
An intriguing feature observed during the flight of feathered animals is the formation of gaps between feathers during the upstroke. These ventilation gaps offer an alternative path with less resistance for air to flow through, reducing the influence of forces opposing the motion. These channels close during the downstroke, allowing the wing to provide the required aerodynamic forces. We describe a mechanism to open these channels for feathers located in the innermost sections of the wing based on the inertial loads imposed by the flapping motion, which increases along the wing-span and allows the distal feathers to deflect more than its adjacent proximal feather. This effect occurs only in one direction, as in the opposite direction the deflection is limited by the contact forces in the overlap region. This mechanism requires modeling the feathers as flexible structural members. Therefore, we develop a model for the flexible feather from a flapping-wing to investigate the formation of ventilation gaps based on the Absolute Nodal Coordinate Formulation, which is a multi-body approach suited for the analysis of structures subjected to large displacements and deflections.
Keywords: Absolute Nodal Coordinate Formulation; Contact; FWUAV; Multi-Body Dynamics; Ventilation